An evaluation of several diet acidifiers commonly utilized in pig starter diets to improve growth performance - Bergstrom, J.R.; Loughmiller, J.A.; Musser, R.E.; Nessmith, W.B.Jr; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Early-weaned pigs (weaned at 14 d of age) that are managed in a conventional one-site production system and fed a complex segregated early-weaning diet will benefit from the inclusion of a diet acidifier during the first week. However, the data indicate no benefit from including a diet acidifier in semicomplex diets fed during subsequent growth phases.
Keywords: Swine; Weanling pigs; Growth performance; Diet acidifiers